Financial Protection Against Medical Expense - Owen O'Donnell (Tinbergen Institute, 2019)
Financial protection is claimed to be an important objective of health policy. Yet there is a lack of clarity about what it is and no consensus on how to measure it. I address the ambiguity of meaning by considering three questions: Protection of what? Protection against what? Protection with what? The proposed answers lead to the suggestion that financial protection is about shielding nonmedical consumption from the cost of healthcare using formal health insurance and public finances, as well as informal and self insurance mechanisms that do not impair earnings potential. Given this definition, I evaluate four approaches to the measurement of financial protection: a) consumption smoothing over health shocks; b) the risk premium; c) catastrophic healthcare payments; and, d) impoverishing healthcare payments. The first of these does not restrict attention to medical expenses, which limits its relevance to health financing policy. The second rests on assumptions about risk preferences. No measure is entirely satisfactory in its treatment of medical expenses that are financed through informal and self insurance instruments. By ignoring these sources of imperfect insurance, the catastrophic payments measure overstates the impact of out-of-pocket medical expenses on living standards, while the impoverishment measure does not credibly identify poverty caused by them. It is better thought of as a correction to the measurement of poverty.
Keywords: D12; D31; D80; I13; I15; 330; health policy; financial protection; medical expenses; catastrophic payments; poverty